Is Biodiversity Attractive? : on-site perception of recreational and biodiversity values in urban green space - Lindberg, Stefan (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2013)
Urban and near-urban green spaces tend to be the main venues for human leisure and recreational activities, given their multifunctional potential, restorative effect and proximity to large numbers of people. Urban green spaces also provide significant ecological resources, not only in contrast to the rest of the urban matrix, but also as a unique part of a greater network of ecosystems. Urban areas have been proven to harbor large numbers of plant and animal species and green spaces are their primary habitats. As global biodiversity is declining and urban populations are growing, urban green spaces play an important role in promoting both biodiversity and human recreation, thus raising the question of how to best combine these functions. It is therefore crucial to understand if and how humans perceive and appreciate biodiversity in a recreational context. Three different types of on-site studies were conducted in an urban park with a wide range of green space typologies. The first study was an inventory and assessment of biodiversity values at the study site, which resulted in a number of zones of varying habitat quality. The other two studies were perception studies, each employing one group of laypersons and one group of landscape/ecology experts. In one of these studies, the participants were asked to photograph features that they liked and disliked along a marked trail. In the other study, the participants instead photographed features of high and low perceived species richness. The photographs and accompanying written motivations were then analyzed based on their spatial distribution and on thematic categories developed from photograph content and motivations. The relationship between the three studies is the primary focus of the thesis. The results suggest a general ability among both experts and laypersons to perceive differences in habitat quality, although their preferences do not necessarily relate positively to high biodiversity values. Further is indicated a strong influence of individual green space elements and details on both species richness perception and preference. The participants appeared to find the study site especially sensitive to human-related elements, which had a significant impact on preference.